Presence of the past : memory, heritage and childhood in post-war Britain - Krips, Valerie, 1939- (Garland, 2000)
This book studies the interaction of heritage and fiction written for children over a forty year period in Britain. Examples range from new interactive displays in museums to historical re-enactment and the teaching of 'living history'.
Keywords: Children's literature, English -- Great Britain -- History and criticism.; English literature -- 20th century -- History and criticism.; History in literature.; Children's literature, English -- History and criticism.; Littérature de jeunesse anglaise -- Histoire et critique.; Littérature anglaise -- 20e siècle -- Histoire et critique.; Histoire dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Children's literature, English; English literature; History in literature; Great Britain; 1900-1999; History; Criticism, interpretation, etc.